Organizational and Economic Mechanism of Digital Finance Asset Market - A. I. Bolvachev; A. F. Leshcninskayа; K. A. Koshelev (Вестник Российского экономического университета имени Г. В. Плеханова)
The market of digital assets and especially market of digital finance assets posses a certain potential, however its development in Russia goes on at a moderate speed and requires specific conditions for realization. The use of digital assets is stipulated by economic benefits connected with speed, simplicity and comfort of issuing digital finance assets in circulation. The article analyzes expediency of applying complex and system approach and their combination to work out organizational and economic mechanism necessary to develop the market of digital finance assets aiming at progress of the new digital environment. The authors suggest considering the Government of the Russian Federation, bodies of economic development of Russia (on federal, regional and local level), other state bodies, autonomous institutions and key business enterprises, which control the economic development of the country as entities on the market of digital finance assts. The mechanism consists of 6 blocks that define key strategies of shaping and developing the market, elaborate trends of investment activity, formulate organizational and economic conditions of market functioning, provide infrastructure development and introduce stimulating measures. The authors put forward a form of organizational and economic mechanism to develop digital finance asset market, which identifies interconnections and interdependence of structural elements on market. This mechanism will fix strategic priorities of developing the market of digital finance assets in the Russian Federation.